English Language Teacher Professional Development: Teacher Educators’ Perceptions and Experiences - Saud, Dammar Singh (Bodhi: An Interdisciplinary Journal, 2023)
With rapid changes and advancements in teaching English language education and the needs of learners, it has become essential for English as a Foreign Language (EFL) teachers to be updated periodically by enhancing their attitudes, skills, and knowledge through different teacher professional development activities and strategies. English language teachers are required to keep upgrading themselves to help EFL learners acquire English effectively. This research aims to explore EFL teacher educators’ perceptions of the importance of teacher professional development and identify their experienced activities for teacher professional development. This research is conducted at a university in Nepal with the participation of eight EFL teacher educators involved in individual interviews. The interpretive research paradigm and case study research method are used for the study. Semi-structured interviews and thematic analysis are used for data collection and analysis. The results show that most of them have positive perceptions towards the importance of EFL professional development and offer suggestions on activities for English proficiency, teaching pedagogy, digital skills, and research skills for teacher professional development that administrators of the university can consult to build skilled teaching professionals who can meet various needs of present learners.